Costs, burden and quality of life associated with informal caregiving for children with Lymphoma attending a tertiary hospital in Ghana. (December 2020) - Dawson, Cromwell Prince; Aryeetey, Genevieve Cecilia; Agyemang, Samuel Agyei; Mensah, Kofi; Addo, Rebecca; Nonvignon, Justice
Introduction: Primary family caregivers provide substantial support in the management of lymphoma, potentially affecting their quality of life and increasing household health care costs. Our aim was thus to determine the economic costs and quality of life of primary caregivers of children with lymphoma. Methods: This cross-sectional study involved primary informal caregivers of children with lymphoma attending the pediatric cancer unit at Komfo Anokye Teaching Hospital. The study adopted a cost-of-illness approach to estimate the direct costs (medical and non- medical) incurred and indirect cost (productive losses) to caregivers over the one-month period preceding the data collection. Zarit Burden Interview was used to determine caregiver burden and EUROHIS-QoL tool was used to determine the quality of life of primary caregivers. Results: The average cost of managing lymphoma in children was estimated to be US440.32, 97% of which were direct costs. On average, caregiver burden was 26.3 on the scale of 0 to 48. About 94% of caregivers reported high burden, with more males reporting high burden. Overall, average quality of life among caregivers was 2.20 on the 1 to 5 range. Approximately 85% of respondents reported low quality of life, with females reporting lower quality of life than males. Discussion: This study shows that lymphoma is associated with substantial cost and increased burden, and affects quality of life of family caregivers. Future studies can explore the impact of social protection interventions (in the form of health insurance) to reduce the household economic burden of managing lymphoma in children.